ANTI HYPERLIPIDEMIC ACTIVITY OF SPONDIAS PINNATA FRUIT EXTRACTS (International Journal of Pharmaceutical Sciences and Drug Research, 2017)
Hyperlipidemia is the greatest risk factor of coronary heart disease. Medicinal plants play a major role in hypolipidemic activity. Literature claims that Saponins are able to reduce hyperlipidemia. Based on high saponin content in herbal plants, Spondias pinnata (SP) was selected and the present study focus on the anti-hyperlipidemic activity of methanolic extracts of fruits of SP against Triton induced hyperlipidemia in rats. SP was administered at a dose of 100 and 200 mg/kg (p.o) to Triton induced hyperlipidemic rats. Fenofibrate was used as reference standard. The statistical analyses were carried out using one way ANOVA followed by Dunnet’s multiple comparisons test. The present investigation shows that all triton induced rats displayed hyperlipidemia as shown by their elevated levels of serum and liver cholesterol, triglyceride, PL, VLDL, LDL and the reduction in the HDL level. It can be concluded that SP 100 and 200 mg/kg treatment was effective in cholesterol, PL, TG, VLDL, LDL and HDL in a dose dependant manner.